Botany And Metaphor - Ahmed Fauzi, Tetriana (2012)
I started the doctorate program with works depicting fictional plants as a mirror or metaphor for my thoughts and feelings. The plants in the watercolour works on paper are impossible biologically and in terms of the environments in which I place them. In connection with these artworks I looked at the work of Charles Avery and Marcel Boodthaers, who both put their artwork in a fictional frame of an invented island and an imaginary museum using different methods and media. Charles Avery exhibits drawings, sculpture and text to realize his imaginary island, while Broodthaers uses readymade objects to create his fictional museum. I wanted the plants I make to have the quality that, although they are fiction, they can possibly exist in the mind of the viewer.